Penguatan Karakter Islami Siswa melalui Kegiatan Ekstrakurikuler di MIN 1 Lhokseumawe - Juniar, Cut Maulinda; Shaliha, Amila (Pascasarjana IAIN Lhokseumawe, 2025)
This study is grounded in the importance of strengthening students’ character through the integration of Islamic values and local culture within the madrasah environment. At MIN 1 Kota Lhokseumawe, the synergy between Islamic principles and Acehnese cultural values serves as a strategic foundation for realizing holistic and context-based character education. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The research informants consisted of the principal, extracurricular supervisors, and students. Data were analyzed through three main stages: data condensation, data display, and conclusion drawing, with validation conducted through source and method triangulation. The findings indicate that the integration of Islamic values and local culture at MIN 1 Kota Lhokseumawe is implemented through four systematic stages: (1) formulation of school policies emphasizing an Islamic character vision and local wisdom; (2) implementation of instructional and extracurricular activities based on Islamic values; (3) internalization of values through social practices, worship, and cultural activities; and (4) continuous evaluation conducted by teachers and the school administration. The model of integrating Islamic and local cultural values has been proven to strengthen students’ holistic character formation, fostering a balance between ḥablum minallāh (relationship with God) and ḥablum minannās (relationship with others). The study also recommends the development of a digital system for documenting and evaluating character-building activities to enhance the effectiveness and sustainability of Islamic values implementation in madrasah education.